2018
DOI: 10.1016/j.celrep.2018.11.065
|View full text |Cite
|
Sign up to set email alerts
|

KLF4, A Gene Regulating Prostate Stem Cell Homeostasis, Is a Barrier to Malignant Progression and Predictor of Good Prognosis in Prostate Cancer

Abstract: SUMMARY There is a considerable need to identify those individuals with prostate cancer who have indolent disease. We propose that genes that control adult stem cell homeostasis in organs with slow turnover, such as the prostate, control cancer fate. One such gene, KLF4, overexpressed in murine prostate stem cells, regulates their homeostasis, blocks malignant transformation, and controls the self-renewal of tumor-initiating cells. KLF4 loss induces the molecular features of aggressive cancer and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…In maintaining PCa stem cell homeostasis, mixed lineage kinase 3 (MLK-3), a MAPK member, promotes β-catenin's interacts with KLF4 instead of TCF, and finally reduces EMT initiation [150][151][152]. When in circulation, PCa cells need to overcome nutrient limits, which might cause tumor necrosis.…”
Section: How Ras/wnt Crosstalk Affect Pca Bmmentioning
confidence: 99%
“…In maintaining PCa stem cell homeostasis, mixed lineage kinase 3 (MLK-3), a MAPK member, promotes β-catenin's interacts with KLF4 instead of TCF, and finally reduces EMT initiation [150][151][152]. When in circulation, PCa cells need to overcome nutrient limits, which might cause tumor necrosis.…”
Section: How Ras/wnt Crosstalk Affect Pca Bmmentioning
confidence: 99%
“…We also examined if upregulation of MED19 could promote the proliferation of other early stage prostate cancer cell lines. Indeed, we found that overexpression of MED19 increased proliferation (as well as colony formation) in non-malignant RWPE-1 cells (Fig 2A and S2A Fig), but did not affect the growth of RWPE-2 cells, which are a malignant derivative of RWPE-1 cells, transformed with RAS (Fig 2B and S2B Fig) [31]. This is in spite of similar levels of MED19 protein expressed in RWPE-1 cells and RWPE-2 cells (S3 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…RWPE-1 cells and RWPE-2 cells were cultured in keratinocyte SFM media supplemented with L-glutamine, BPE, and EGF (ThermoFisher Scientific) [63]. The mouse prostate stem cell line expressing activated AKT was cultured as described in [31]. R1881 (Perkin Elmer) was reconstituted in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the above contradictions can be at least partially resolved by the discovery that the levels of KLF4 vary depending on the subtype of prostate cancer [ 100 ]. KLF4 is highly expressed in indolent tumors which do not cause any symptoms and do not require any treatment but is absent from aggressive prostate tumors.…”
Section: Prostate Cancermentioning
confidence: 99%
“…The reduced expression of KLF4 is associated with the molecular features of aggressive cancers. Accordingly, induction of KLF4 in established tumors reverses their aggressive phenotype [ 100 ]. KLF4 thus blocks the malignant transformation and impedes tumor progression.…”
Section: Prostate Cancermentioning
confidence: 99%